The Work of the Inter-American Juridical Committee - Negro Alvarado, Dante (2015)
The present article takes up previous publications on the work of the Inter-American JuridicalCommittee. This time, we will take on the activities of that organ of the Organization of American States during the years 2012, 2013 and 2014, particularly, the development of such important topics for the legal agenda of the inter-American system such as the strengthening of the inter- American human rights system, the simplified stock corporations and the model legislation proposed by the Inter-American Juridical Committee on that topic, the social responsibility of companies in the area of human rights and the environment, the protection of cultural property in cases of armed conflict and the model legislation proposed by the Committee on that issue, the cultural diversity in the development of international law and the guidelines prepared by theCommittee, among other topics.